Comparison of oral and maxillofacial trauma during the first and third lockdown of the COVID-19 pandemic in the United Kingdom. Issue 4 (May 2022) - Puglia, F.A.; Chiu, G.A.
Abstract: The incidence and management of maxillofacial trauma was compared between the first and third lockdowns in the United Kingdom due to the COVID-19 pandemic. From 6 January, 2021 to 8 March 2021, the units that had participated in the collection of data during the first lockdown were asked to update their information into the same database for the third. Nine units participated with 929 entries. Compared to the first lockdown, the number of patients whose treatment had been changed due to the pandemic reduced from 7.6% to 0.4% in the third lockdown. In the UK during the third lockdown there were higher numbers infected with COVID-19 and admitted to hospital than in the first lockdown. Despite this OMFS units that participated in the second study were able to continue the management of maxillofacial trauma without the pandemic affecting care.